Perceived Quality Dalam Membentuk Customer Loyalty Melalui Brand Equity Sebagai Variabel Intervening (Studi Kasus Pengguna Smartphone Xiaomi di Desa Mangunan, Kecamatan Udanawu, Kabupaten Blitar) - An’am, Ahmad Khafidul; Mansur, Muhammad; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of perceived quality, customer loyalty, brand equity on Xioami smartphone users. The research used is a descriptive quantitative method with an explanatory research approach. The population in this study is the people of Mangunan Village, Udanawu District, Blitar Regency with a total population of 3,589. While the sample formula used is using the slovin formula with a purposive sampling approach with a total of 98 samples. The sample that is focused in this research is Xiaomi smartphone users. The data used is primary data using a questionnaire distributed to respondents. The data analysis method used is instrument test; validity test, reliability test, normality test, path analysis test, hypothesis test: partial t test, Sobel test. From the results of the study simultaneously obtained results that perceived quality (perceived quality) has an indirect effect on customer loyalty (consumer loyalty) through brand equity (brand equity) as an intervening variable or intermediate variable. Keywords: Perceived Quality, Customer Loyalty, Brand Equity